Japan : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Japanese economy has shown robust growth after the March 2011 Great East Japan earthquake. Post-earthquake, Japan has had to deal with devastating human toll and destruction, while businesses and households have had to recover from the losses. Exports were impacted by supply chain disruptions, weak global demand, and an appreciation of the yen. The Executive Board noted, however, that despite a weak global demand, the Japanese economy has shown remarkable resilience to severe economic distress and moderate market shocks.